2010
DOI: 10.1097/cej.0b013e32833c1be0
|View full text |Cite
|
Sign up to set email alerts
|

Variations in hemoglobin before colorectal cancer diagnosis

Abstract: We have conducted the present case-control study to examine whether long-term variations in blood hemoglobin (Hb) levels within the normal range could detect subtle gastrointestinal bleeding in the early development of colorectal cancer (CRC). A total of 1074 CRC cases aged 45-75 years that have been diagnosed with CRC and had normal Hb levels were frequency matched for age and sex with cancer-free individuals at a ratio of 10 controls per case. Our retrospective analysis indicates that starting from 4 years p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Previous publications have shown that red blood cell distribution width (RDW) had 84% sensitivity and 88% specificity for right-sided CRC cases; no improved sensitivity in combination with red cell distribution width (RDW), hemoglobin (Hgb), and mean corpuscular volume (MCV) was documented [10]. Goldshtein et al [18] have shown that a minor decrement in the levels of blood Hgb may signify the early development of CRC. Recognition of a change in Hgb levels over time, rather than the most current value alone, has been shown to improve detection of CRC [19].…”
mentioning
confidence: 99%
“…Previous publications have shown that red blood cell distribution width (RDW) had 84% sensitivity and 88% specificity for right-sided CRC cases; no improved sensitivity in combination with red cell distribution width (RDW), hemoglobin (Hgb), and mean corpuscular volume (MCV) was documented [10]. Goldshtein et al [18] have shown that a minor decrement in the levels of blood Hgb may signify the early development of CRC. Recognition of a change in Hgb levels over time, rather than the most current value alone, has been shown to improve detection of CRC [19].…”
mentioning
confidence: 99%
“…In the 39 studies that used a single FBC test, three used the first set of FBC measurements available from entry into the study, six used the last available FBC set (the one closest to the time of diagnosis), and it was unclear in the remaining 30 studies. Of the three studies that used multiple sets of FBCs, Boursi 2016 [ 20 ] and Kinar 2016 [ 40 ] developed a prediction model and Goldshtein 2010 [ 27 ] did not.…”
Section: Resultsmentioning
confidence: 99%
“…Goldshtein 2010 [27] performed a mixed effects analysis to model changes in haemoglobin levels between those with and without a colorectal cancer diagnosis over 10 years before diagnosis, in an Israeli population. Using a logarithmic transformation of time, the mixed model for those with a diagnosis (slope = 0.3, intercept = 12.72) indicated a greater decline in haemoglobin than those without (slope = 0.04, intercept = 13.111).…”
Section: Repeated Fbc Measuresmentioning
confidence: 99%
“…Ideally, a patient specific approach would be taken for the interpretation of laboratory results, because historic data from the patient of interest is the best indicator of the normality of the current results [2]. Such a personalized approach would allow small fluctuations to be identified, a desirable characteristic given recent studies showing the predictive power of gradual temporal trends [3, 4]. However, large amounts of patient specific data are rarely available.…”
Section: Introductionmentioning
confidence: 99%